2020
DOI: 10.2196/19338
|View full text |Cite
|
Sign up to set email alerts
|

Digital Response During the COVID-19 Pandemic in Saudi Arabia

Abstract: Background The first case of COVID-19 in Saudi Arabia was confirmed on March 3, 2020. Saudi Arabia, like many other countries worldwide, implemented lockdown of most public and private services in response to the pandemic and established population movement restrictions nationwide. With the implementation of these strict mitigation regulations, technology and digital solutions have enabled the provision of essential services. Objective The aim of this p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
239
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(248 citation statements)
references
References 19 publications
5
239
2
2
Order By: Relevance
“…Hassounah et al. [ 72 ] confirmed that the ministry of health in Saudi Arabia used social media platforms to disseminate correct information about COVID-19 and to distribute health education materials that cover topics related to COVID-19. Shimizu [ 73 ] reported that the media has concentrated on the COVID-19 and considered it as a dangerous threat, which has added to fear, stress, and panic among the public.…”
Section: Discussionmentioning
confidence: 99%
“…Hassounah et al. [ 72 ] confirmed that the ministry of health in Saudi Arabia used social media platforms to disseminate correct information about COVID-19 and to distribute health education materials that cover topics related to COVID-19. Shimizu [ 73 ] reported that the media has concentrated on the COVID-19 and considered it as a dangerous threat, which has added to fear, stress, and panic among the public.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside this, an appreciable investment in technology infrastructure and telehealth in recent years in line with Saudi vision 2030 was made. 67 , 108 This investment resulted in 19 applications and digital platforms in the health care sector being used during the pandemic, facilitating the provision of health services including telemedicine and telecare. 67 In addition, Qassim University had good technology infrastructure and e-learning systems even before the pandemic, and it was considered one of the most active e-learning universities in Saudi Arabia.…”
Section: Discussionmentioning
confidence: 99%
“…Online and distance learning at the schools and universities, 66 as well as working from home, has been facilitated by major investments in digitalization, technology and artificial intelligence in Saudi Arabia in line with its 2030 vision. 67 …”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine is used to deliver real-time communication from a distant place between the doctor and the patient through an electronic device (either phone or video call) [5,16]. Telemedicine was identified as an effective way to deliver medical care during the COVID-19 pandemic, and it can be very helpful for the orthopedic specialty [7][8][9][10]. Telemedicine has been considered successful for delivering care during the COVID-19 pandemic in Saudi Arabia [17].…”
Section: Discussionmentioning
confidence: 99%
“…Patients affected by COVID-19 can receive medical care through these applications. One application, Rest Assured or Tetamman, provides healthcare support mainly to citizens or residents in domestic isolation or quarantine [8]. Another application is Seha which offers consultations and diagnostic services to patients [9].…”
Section: Introductionmentioning
confidence: 99%